2007
DOI: 10.1080/09500690600991149
|View full text |Cite
|
Sign up to set email alerts
|

Upper Secondary Bruneian Science Students’ Perceptions of Assessment

Abstract: The aims of this study were to evaluate reliability and validity of the Students' Perception of Assessment Questionnaire (SPAQ), to evaluate students' perception on assessment, and to evaluate gender-based, grade-based, and ethnicity-based differences in students' perceptions. The validity and reliability coefficients revealed that the SPAQ was suitable for assessing students' perceptions on five assessment dimensions. The average scale-item mean values for all the scales were less than 3.0, which indicates a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 13 publications
2
44
0
Order By: Relevance
“…In addition, Dhindsa, Omar, and Waldrip (2007) found that although students perceived that their classroom assessment tasks aligned with what they learned in class and had transparency, there were low levels of student consultation, authenticity, and diversity, which might be detrimental to self-efficacy. Recently, Alkharusi (2013) showed that high levels of authenticity, transparency, and diversity were significantly associated with self-efficacy and perception of task value.…”
Section: Students' Perceptions Of Assessment Tasksmentioning
confidence: 92%
“…In addition, Dhindsa, Omar, and Waldrip (2007) found that although students perceived that their classroom assessment tasks aligned with what they learned in class and had transparency, there were low levels of student consultation, authenticity, and diversity, which might be detrimental to self-efficacy. Recently, Alkharusi (2013) showed that high levels of authenticity, transparency, and diversity were significantly associated with self-efficacy and perception of task value.…”
Section: Students' Perceptions Of Assessment Tasksmentioning
confidence: 92%
“…For example, Dorman, Fisher, and Waldrip (2006) provided evidence that assessment tasks with a low degree of congruence with planned learning, authenticity, and transparency could have a detrimental effect on students' confidence in their ability to successfully perform academic tasks. In their study of Bruneian secondary school students' perceptions of assessment tasks, Dhindsa, Omar, and Waldrip (2007) found that, despite reports of low levels of student consultation, authenticity, and diversity, students still perceived that classroom assessment tasks were transparent and aligned with classroom teaching. In his study conducted with 198 tenth-grade students in Oman, Alkharusi (2013) found that a high degree of authenticity and transparency in assessment were both positively associated with students' self-efficacy and task value.…”
Section: Students' Perceptions Of Assessmentmentioning
confidence: 95%
“…1 Rochford found significantly higher achievement when instruction material was prepared in response to learning style at an urban community college. 2 Miller observed a significant improvement in examination scores as well as in students' attitude towards learning when information delivery style matched students' learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent assessment approaches are attempting to increase the correspondence between what students need to learn and what is expected for them. 2 The researchers have been constantly pouring the news ideas and innovations in the pond of medical sciences and converting it into ocean of biological sciences.…”
Section: Introductionmentioning
confidence: 99%